International economics - Pugel, Thomas A (McGraw-Hill/Irwin, 2004)
This classic text has sold well for over 35 years because it covers all the conventional areas of international economics in an easy-to-understand manner. The 12th edition has been thoroughly revised and it continues to be accessible, flexible, and interesting to economics and business majors alike. Like earlier editions, it also places international economics events within an historical framework. The overall treatment continues to be intuitive rather than mathematical and is strongly oriented towards policy.